Analisis Redaman Jaringan Fiber To The Home Di Daerah Istana Gardenia Regency - Prasetyo, Iqbal Imadudin; Hidayat, M Reza (Department of Electrical Engineering, UNJANI, 2024)
The need for fiber to the home (FTTH) networks is increasingly being used in urban areas in Indonesia, all big cities need internet to make it easier for residents to carry out activities, one of the areas that uses the FTTH network is the Gardenia Regency Palace, but currently there are still many obstacles in The quality of the network that residents of Istana Gardenia Regency get, therefore it is necessary to check the quality of the FTTH network in the Istana Gardenia Regency area. In this research, a check was carried out on the quality of the attenuation of the FTTH network in the residential area of ​​Istana Gardenia Regency which uses the provider PT. Telkom, this research was carried out by checking network conditions in the field using an optical power meter (OPM) measuring instrument. After checking, the FTTH network was designed using optysystem software and then compared the conditions in the field with the design results. Field measurement results obtained results of 24.46dB at the closest ONT distance and 34.87 at the farthest ONT distance, while simulation results obtained results of 22,527dB at the nearest ONT and 22.668 at the farthest ONT, so it can be seen the influence of the indentation resulting from cable pulling affects the increase. attenuation, after identifying several measurement points, namely at the OLT, ODC, ONT output, the problem is at the farthest ONT output which has an attenuation of 34.87dB, there is an attenuation difference of 12.202dB so repairs are needed at the farthest ONT point in order to have good network quality Keywords : FTTH, Attenuation, Optysystem